Evaluation of the therapeutic potential of several compounds in human herpesvirus 8 using a chimera virus mouse infection model - Rodrigues, Tânia Alexandra da Cruz (2020)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019